Anal Cytology and Human Papillomavirus Genotyping in Women With a History of Lower Genital Tract Neoplasia Compared With Low-Risk Women. Issue 6 (December 2015) - Robison, Katina; Cronin, Beth; Bregar, Amy; Luis, Christine; DiSilvestro, Paul; Schechter, Steven; Pisharodi, Latha; Raker, Christina; Clark, Melissa
Abstract : OBJECTIVE: To compare the prevalence of abnormal anal cytology and high-risk human papillomavirus (HPV) among women with a history of HPV-related genital neoplasia with women without a history of HPV-related genital neoplasia. METHODS: A cross-sectional cohort study was performed from December 2012 to February 2014. Women were recruited from outpatient clinics at an academic medical center. Women with a history of high-grade cervical, vulvar, or vaginal cytology, dysplasia, or cancer were considered the high-risk group. Women with no history of high-grade anogenital dysplasia or cancer were considered the low-risk group. Human immunodeficiency virus–positive women were excluded. Anal cytology and HPV genotyping were performed. Women with abnormal anal cytology were referred for high-resolution anoscopy. RESULTS: There were 190 women in the high-risk group and 83 in the low-risk group. The high-risk group was slightly older: 57 years compared with 47 years ( P =.045); 21.7% of low-risk women had abnormal anal cytology compared with 41.2% of high-risk women ( P =.006). High-risk HPV was detected in the anal canal of 1.2% of the low-risk group compared with 20.8% of the high-risk group ( P <.001). Among women who underwent anoscopy, no anal dysplasia was detected in the low-risk group, whereas 13.4% in the high-risk group had anal dysplasia with 4.2% having anal intraepithelial neoplasia 2 or greater ( P <.001). CONCLUSION: Human immunodeficiency virus–negative women with a history of lower genital tract neoplasia are more likely to have positive anal cytology, anal high-risk HPV, and anal intraepithelial neoplasia. Anal cancer screening should be considered for these high-risk women. LEVEL OF EVIDENCE: II Abstract : Women with a history of genital neoplasia have higher rates of abnormal anal cytology, higher prevalence of anal high-risk human papillomavirus, and more anal dysplasia than women without a history of genital neoplasia.